(untitled) (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2021)
The instilling of Islamic values â€‹â€‹needs to be given by parents to children from a young age so that later the child will have good morals in the environment where he is. This Tarbiyyatul Aulad TPQ helps parents grow their children’s sense of faith in Allah as Muslims, and grow their love for the Prophet Muhammad SAW. Therefore, teachers with knowledge and good manners must be able to motivate, encourage, provide habituation, and provide examples to children. Familiarizing children to read the Koran according to the correct tajwid and makhrajil letters must also be applied from an early age so that later they can istiqomah to read the Koran regularly, for example after praying. Moreover, during this pandemic, we must carry out positive and useful activities so that faith does not decrease and as obedient Muslims, we should always be filled with worshiping Allah.